Simulation and experimental validation of a 9 ton AMB rotor landing in rolling element back-up bearings - Guenther SIEGL (The Japan Society of Mechanical Engineers, 2016)
Backup Bearings (BuB) must be designed to withstand the shock loads which occur during impacts with heavy and/or high-speed rotors. Both experimental testing and transient dynamic simulation are necessary for the study of BuB performance. This paper presents the transient dynamic simulation methodology developed within SIEMENS for the study of full-scale rotor landings in rolling element BuBs. The developed models were validated with a substantial landing program led and performed by SIEMENS, whose objective was to qualify the safe operation of hybrid rolling element BuBs for an industrial application utilizing an AMB-levitated 9 ton supercritical motor. The paper describes the BuB model, summarizes the simulation results and offers a comparison to experimental measurements from the aforementioned successful landing tests program.